Sudden death in athletes: an update - Futterman, L. G.; Myerburg, R. (Sports Medicine, 1998)
The athlete projects the ultimate image of well-being in the health status spectrum. Nevertheless, exercise-related sudden cardiac death (SCD) is an uncommon, yet tragic, occurrence. Exercise-related SCD is defined by symptoms that arise within 1 hour of participation in sport. The major mechanisms involved in exercise-related SCD are related to haemodynamic and electrophysiological changes brought about by exercise in the susceptible individual. Fatal arrhythmia seems to be the most common mechanism of death. Between 1 and 5 cases of SCD per 1 million athletes occur annually. In young athletes (<35 years old), the majority of these cases are caused by defined and hereditary cardiovascular disorders. Among other aetiologies, hypertrophic cardiomyopathy and coronary artery anomalies are most common in this group. In older athletes (>35 years old), sudden death is usually associated with atherosclerotic cardiac disease. A problem for identifying athletes at risk for SCD is that the athlete's heart undergoes adaptive changes in response to regular physical exercise. Alterations in cardiac function influence the physical examination, the electrocardiogram and the echocardiogram. Because of these characteristic 'abnormalities' of the athlete's heart, it is often difficult to distinguish physiological adaptations from pathophysiological processes. Although studies and observations have helped to clarify the cardiovascular pathology responsible for SCD in young, apparently healthy individuals, effective methods for preventing SCD and identifying and screening athletes at risk remain elusive. Problems with routine comprehensive screening of athletes include the limitations inherent in the predictive value of available diagnostic procedures and the cost of testing large populations. The variation from normal cardiac physiology found within the athletic population and the rarity of SCD in athletes means that elaborate screening to determine individuals at risk is neither practical nor cost effective. A thorough assessment of pertinent family and medical histories, cardiac auscultation of young athletes, evaluation of exercise-induced symptoms and education of older athletes to the symptoms of cardiac ischaemia are all essential to primary prevention of SCD in the athletic population. Until reliable methods can accurately identify those athletes at risk for SCD, broad recommendations are available to help guide the management and participation in sports of athletes with cardiovascular disease.